Pelatihan Trik Menciptakan Peluang Usaha Untuk Karyawan Bumnag Kenagarian Malay V Suku Timur - Yusnaena Yusnaena; Haryeni, Erdasti Husni, Deddi Julianto (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2019)
The Nagari-owned business entity is renamed Malay V Eastern Tribe. based on the results of interviews in the field, it indicates that this business entity has not been productive at all, no business has been carried out. existing capital does not yet function to grow the economy of the community, even though based on historical data there are many fields of business that can be fostered, because this livelihood is a productive livelihood, but this does not correlate with enthusiasm in managing this rural business entity, the results of our interviews with Walinagari It seems that people are confused and have not found entrepreneurial activities like what they will do to produce this Alumni Department. Based on the above phenomena, our team will provide training and counseling to the Eastern Tribal Kenagarian Malay V community to provide knowledge on how to create an entrepreneur, which we pack in topic